2020
DOI: 10.1097/iop.0000000000001734
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing 3D-Printed Orbital Floor Stamps to Create Patient-Specific Implants for Orbital Floor Reconstruction

Abstract: Purpose: This study seeks to test a novel technique of custom-printed midface contour models with orbital floor “stamps” to guide reconstruction of orbital floor blowout fractures, with or without concomitant zygomaticomaxillary complex injury. Methods: A series of 4 consecutive patients with orbital floor blowout fractures (including 3 with zygomatic maxillary complex fractures) were retrospectively examined for outcomes associated with orbital floor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Current investigations into 3D printing technology explore its viability for crafting personalized orbital implants, with a significant body of research focusing on utilizing 3D models for implant customization [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] and for the creation of directly printed implants [ 45 , 46 , 47 , 48 , 49 , 50 ]. Chai et al (2021) demonstrated the efficacy of using patient-specific 3D-printed models as templates for intraoperative adjustments to implants, noting a marked decrease in both surgery duration and related complications [ 32 ].…”
Section: Applications Of 3d Printing In Oculoplastic and Orbital Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Current investigations into 3D printing technology explore its viability for crafting personalized orbital implants, with a significant body of research focusing on utilizing 3D models for implant customization [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] and for the creation of directly printed implants [ 45 , 46 , 47 , 48 , 49 , 50 ]. Chai et al (2021) demonstrated the efficacy of using patient-specific 3D-printed models as templates for intraoperative adjustments to implants, noting a marked decrease in both surgery duration and related complications [ 32 ].…”
Section: Applications Of 3d Printing In Oculoplastic and Orbital Surgerymentioning
confidence: 99%
“…Finally, a 3D-printed pressing apparatus designed to press a real implant between two 3D models of the implant is explored. Rather than the surgeon cutting or molding the implant, they hold and press the apparatus to obtain a ready-to-use personalized implant [ 41 , 42 ]. Though not directly compared to 3D-printed templates or molds, this technique shows excellent outcomes through quantitative [ 42 ] and qualitative [ 41 ] measures.…”
Section: Applications Of 3d Printing In Oculoplastic and Orbital Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…To account for this issue, we developed positive and negative molds of the orbital floor to stamp the plate to achieve higher fidelity in our implants. 2 In addition, we have found that heat-activated poly- d -lactic acid implants were more easily able to achieve a perfect contour of the mirrored orbital floor model. We initially confirmed fidelity of these stamped implants within an orbital model; however, with experience, we found that this step could be omitted, and we have since used stamps in isolation (Fig.…”
mentioning
confidence: 91%
“…We greatly appreciate the interest in our article 1 and the response by Mr. Prabhu and Dr. Runyan. In their letter and a recently published article, 2 they describe the use of molds with which titanium orbital fixation plates can be shaped. Using both positive and negative molds of the orbital floor, they compress the plate and, much like an industrial manufacturing machine, stamp it into the desired shape.…”
mentioning
confidence: 99%